2014
DOI: 10.1017/s1041610214001148
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral correlates of anxiety in well-functioning older adults

Abstract: Anxiety in older adults is not only linked to poor health, but also to dysfunctional social behavior, loneliness, boredom and experiential avoidance. Maladaptive profiles of older adults with regard to these variables have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The standard deviations for the random slopes were 1.04, 1.18, and 1.49, respectively. other hand, when taking into account all of the confinement time, it seems that age as a predictor variable becomes more important, as pointed out by other studies (8,30). Young students may have initially suffered more depressive symptoms, as their lives were more affected when their daily routines were abruptly interrupted.…”
Section: Discussionmentioning
confidence: 87%
“…The standard deviations for the random slopes were 1.04, 1.18, and 1.49, respectively. other hand, when taking into account all of the confinement time, it seems that age as a predictor variable becomes more important, as pointed out by other studies (8,30). Young students may have initially suffered more depressive symptoms, as their lives were more affected when their daily routines were abruptly interrupted.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, engagement in EA may prevent some older adults from seeking help for their mental and physical health problems. Losada et al. (2015) also demonstrated a significant, positive relationship between anxiety symptomatology and EA in older adults.…”
mentioning
confidence: 73%
“…It is hard to discern whether loneliness is the cause or consequence of these psychological characteristics since hardly any longitudinal research has explored that question. Losada et al (2012, 2015) as well as Cohen-Mansfield & Parpura-Gill (2007) reported that loneliness and mental health are connected.…”
mentioning
confidence: 99%